English in the digital age : information and communications technology (ICT) and the teaching of English - Goodwyn, Andrew, 1954- (Cassell education., 2000)
New communications technology has been a boon to teaching and learning subjects of English, from reading and writing to literature such as Shakespeare. This book explores the ways that information and communications technology, or ICT, can be employed in teaching English and enriching the abilities of students. What are the advantages of ICT, and what are some of the concerns? Contributors from Europe, Australia, and North America address the use of media in teaching, from video, film, and audiotape to computer games and online resources. English in the Digital Age surveys the ways ICT is pres.